Breakfast Skipping and Obesity Risk among Urban Adults in Bangladesh - Shatabdi Goon; Md. Saiful Islam (Intelektual Pustaka Media Utama, 2014)
Positive association between skipping breakfast and overweight and obesity is globally observed regardless of cultural diversity among countries. A cross-sectional descriptive study was performed on a total of 426 urban adults, who were randomly selected in a nutrition counseling center of Dhaka city, Bangladesh. The objective of this study was determining the association between breakfast skipping and obesity risk in urban adults of Bangladesh. Results indicated that approximately 35.2% of the sample skipped breakfast. Gender was the only statistically significant sociodemographic variable, with females skipping at two times the rate of males (OR 95% CI: 1.9; 1.3-2.9). Obesity was detected among 39.5% of breakfast skippers and they showed significantly high prevalence (X2=30.15, p<0.05). Skippers were significantly more likely being obese (OR 3.5; 95% CI 2.2-5.5) and obesity was more prevalent in female skippers (X2=8.7, p<0.05), with three times more compared to male skippers (OR 95% CI: 2.8; 1.4-5.9). Breakfast skipping is highly prevalent among urban adult population with significant association of obesity in Bangladesh. Health promotion strategies should be used to encourage all adults to eat breakfast regularly.